Trade with Nominal Rigidities: Understanding the Unemployment and Welfare Effects of the China Shock - Rodríguez-Clare, Andrés; Ulate, Mauricio; Vásquez, José P. (Journal of Political Economy, 2026)
We present a dynamic quantitative trade and migration model that incorporates downward nominal wage rigidities and show how this framework can generate changes in unemployment and labor participation that match those uncovered by the empirical literature studying the China shock. We find that the China shock leads to average welfare increases in most US states, including many that experience unemployment during the transition. However, nominal rigidities reduce the overall US gains by around two-thirds. In addition, there are 18 states that experience welfare losses in the presence of downward nominal wage rigidity that would have experienced gains without it.